Controlling Assessment of Disinfection by Products in Drinking Water - A Review - Qasim, Ban; Abdul Syukor, Abd Razak; Siddique, Md. Nurul Islam; Suryati, Sulaiman; Nur Hamizah, H. (IJISET, 2015)
The treatment and distribution of drinking water for a safe use is one of the greatest achievements of our twentieth century. Drinking water disinfection and treatment is the most successful measurement to reduce water born and bacteria that cause many disease and it is the most effective way to protect health. Before the beginning of drinking water treatment and disinfection history, many diseases had been killed thousands of people around the world and until now many people around the world have no appropriate access to clean drinking water. According to World Health Organization (WHO), in 2012, 748 million people still relied on unimproved drinking water source. It is known that water disinfection is very important and inescapable step in water treatment process to ensure safe drinking water that is leads to the formation of disinfection - by products (DBPs). Many disinfections by products are detected in drinking water, and they are usually grouped into the following categories: Trihalomethans (THMs), Haloacetic acid (HAAS) Inorganic disinfections by - products (bromate and chlorite).